Inner galactic disc metallicity distributions and the bulge-disc relation - Haywood M.; Gómez A.; Babusiaux C.; Hill V.; Katz D.; Royer F. (EPJ Web of Conferences, 2012)
The intermediate-to-old population of the inner galactic disk remains a relatively uncharted territory. We present the results of a high resolution spectroscopic survey of over 200 red clump stars in the inner galactic disc (3–5 kpc from the galactic centre, Z ≤ 300pc from the plane). The metallicity distribution of the sample is clearly more metal-rich than the solar neighborhood, implying a significant radial gradient in the galactic disc at the intermediate ages probed by red clump stars. We discuss the implications of these results on the existence of gradients and their flattening with age. Finally, for the first time, this result brings support to the idea that the metal rich part of the bulge MDF may originate from the inner disk through dynamical instabilities.